Comparison of biomarkers of COVID-19 patients with the alpha variant (B.1.1.7), the delta variant (B.1.617), and no mutation detected - Karadağ Gencer, Sanem (The European Research Journal, 2023)
Objectives: We aimed to compare biomarkers of COVID-19 patients with the Alpha variant (B.1.1.7), the Delta variant (B.1.617), and no mutation detected in our study. Methods: A total of 600 patients with positive COVID PCR test and Alpha, Delta variant and no mutation detected with Covid PCR mutation test were included in the study. Troponin I, creatinine, Alanine Aminotransferase (ALT), Aspartate Aminotransferase (AST), Lactate Dehydrogenase (LDH), fibrinogen, D-dimer, ferritin, number of lymphocytes, lymphocytes (%), platelet (PLT), mean platelet volume (MPV), platelet distribution width (PDW), trombosite ratio in the blood (PCT), C-reactive protein (CRP) values were analyzed retrospectively. The age, gender, and hospitalization of the patients were evaluated concurrently. Results: Age, troponin, creatinine, LDH, PLT, MPV, and D-dimer were laboratory parameters that vary significantly with COVID-19 virus mutation. Age, troponin, LDH, and MPV values were lower in patients with Delta variant according to patients with the Alpha variant. Lymphocytes (N) and lymphocytes (%) values were lower in hospitalized patients relative to outpatients while age, troponin, LDH, CRP, and D-dimer values were higher in hospitalized patients than outpatients irrespective of mutation. Creatinine values were higher only in hospitalized patients with no mutation detected while ferritin and fibrinogen values were higher in hospitalized patients with Delta variant and no mutation detected. Conclusions: Age, troponin, creatinine, LDH, PLT, MPV, D-dimer, fibrinogen, ferritin, CRP, lymphocytes (N), and lymphocytes (%) values can guide to evaluate the diagnosis and hospitalization of patients with future different mutations.